Removal of Cr(III) and Cr(VI) from Aqueous Solution by Biosorption Using Agricultural Waste Materials: Batch and Continuous Reactor Study - Jyoti Sarma, Pranab; Kumar, Rajneesh; Arul Manikandan, N.; Pakshirajan, Kannan (Asian Journal of Chemistry, 2015)
In this study, different agricultural waste materials, namely rice husk, sugarcane bagasse, mustard oil cake, tea waste, betel nut peel and saw dust, were investigated for their potential to remove Cr(III) and Cr(VI) from aqueous solutions. The effect of solution pH, contact time, biosorbent dosage and initial Cr(III)/Cr(VI) concentration on its biosorption was first studied under batch condition. Among the six biosorbents tested in this study, sugarcane bagasse removed Cr(III) with a maximum efficiency of 89.14 %, whereas rice husk yielded a maximum Cr(VI) removal efficiency of 79.48 % under the batch condition. Chromium sorption kinetics was best explained by the intra particle diffusion based second order kinetics model. Fourier transform infrared, scanning electron microscope analyses of sugarcane bagasse and rice husk were performed before and after its chromium loading in order to analyze the morphology and the functional groups responsible for the chromium biosorption. Continuous column sorption of Cr(III) and Cr(VI) were carried out in two identical fixed-bed columns with sugarcane bagasse and rice husk, respectively, as the biosorbents. The influence of bed depth and flow rate on continuous chromium sorption was investigated at 30 mg L–1 inlet concentration. The chromium breakthrough and saturation time in both the columns increased with a decrease in the flow rate from 30 to 10 mL min–1. The same effect was observed with an increase in the column bed depth from 10 to 30 cm.